Penjan 4 : Penyan - Hakimi, Halim (UNIMAS Publisher, 2024)
Penyan is a Bidayuh term that translates to "window". This wall installation piece integrates found objects, particularly old windows, to convey the inner conflict of the artist while addressing matters of national identity, culture, religion, and the regional nuances that intersect within the artist's own identity. It symbolizes the interplay between Malaysia and regional influences.